Analysis of Blended Learning Development in Distance Learning in Variation of Borg & Gall and Addie Models - Untoroseto, Dedi; Triayudi, Agung (Newinera Publisher, 2023)
With the success of blended learning and the use of online media on learning outcomes and from article search results, it shows that there have been many articles that contain blended learning and various media uses, and reviews are needed about it by reviewing existing articles or commonly called literature reviews. Borg & Gall and ADDIE models. The Borg & Gall model and ADDIE are two teaching models used in colleges and universities. ADDIE stands for Analyze, Design, Development, Implementation, and Evaluation. In the Borg & Gall model, the steps taken are research and information. Research and information is used to collect information about the need for learning evaluation instruments for learning media development courses for students. In the ADDIE model the steps taken are the same as the original which includes aspects of Analyze, Design, Development, Implementation, and Evaluation. Thus, what is needed in this development is a reference about the product procedure to be developed. The description of the development model of Borg and Gall, described as follows; Educational research and development (R&D) is the process used to develop and validate educational products. The validity of interactive blended learning is: (1) according to expert reviews the content of metrics shows a good category (92%), (2) according to expert reviews learning design is in the good category (88%), (3) according to expert reviews learning media shows a good category (86%), Thus, this interactive blended eLearning does not need to be revised and can be used for further research.